PERILAKU KONDUKTIVITAS TANAH (EC) TERHADAP PEMBERIAN KADAR AIR DAN KADAR NPK KHUSUSNYA TANAH LEMPUNG - Angga Defrian; Zulfakri Zulfakri; Agus Susanto Ginting; Hasbi Mubarak Suud (JURNAL AGROTEKNOSAINS, 2023)
EC measurement tool has been made on soil fertility based Arduino Uno microcontroller ATmega328. These devices use voltage sensors, and amperes. This measuring instrument consists of the unit UNO Mmikrokontroler ATMega 328, SD Card, Volt, Ampere, and RTC. Early research methods include the design, manufacture and testing of devices. After testing this device will monitor the Volts, amperes, which will be converted EC, the test is still in the prototype in the soil resistivity measuring box and conducted testing on the moisture content (8%). This prototype tool is equipped with a data logger system as a measurement data storage to SD card. Data storage is done every 5 seconds and in this study conducted for 2 hours. A thorough soil Sample is sandy loam soil.